2020
DOI: 10.3390/ani10112018
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Replacing Wildrye Hay with Mulberry Leaves on the Growth Performance, Blood Metabolites, and Carcass Characteristics of Sheep

Abstract: The objective of this study was to evaluate the effects of partially substituting for conventional forage, Chinese wildrye (CW), with mulberry leaves (ML) on the growth, digestion, ruminal fermentation, blood metabolites, and meat quality of sheep in a 65-day feedlot study. Thirty-two four-month-old male small-tailed Han sheep (25.15 ± 1.03 kg) were randomly assigned to one of four treatments. The dietary treatments consisted of four proportions of ML (0, 8, 24, and 32%) as a substitute for CW (designated as M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 54 publications
(55 reference statements)
3
21
0
Order By: Relevance
“…Therefore, IMF was not only one of the nutrients but also a high content of IMF was beneficial to improve the edible quality of meat. There were some ways to increase IMF content, for example, Sun et al (2020) suggested that the IMF deposition of sheep was promoted by mulberry leaves diets which may be related to the fact that mulberry leaf flavonoids can increase insulin levels in animals. Yang et al (2019) indicated a higher dosage of nicotinic acid dietary increased the IMF deposition by upregulating the expression of genes related to adipocyte differentiation, adipogenesis, and lipid and glucose metabolism based on transcriptomics.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, IMF was not only one of the nutrients but also a high content of IMF was beneficial to improve the edible quality of meat. There were some ways to increase IMF content, for example, Sun et al (2020) suggested that the IMF deposition of sheep was promoted by mulberry leaves diets which may be related to the fact that mulberry leaf flavonoids can increase insulin levels in animals. Yang et al (2019) indicated a higher dosage of nicotinic acid dietary increased the IMF deposition by upregulating the expression of genes related to adipocyte differentiation, adipogenesis, and lipid and glucose metabolism based on transcriptomics.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ensiling of mulberry leaves and utilization in the ruminant's diet could be possible without affecting the DMI. However, a recent study of Sun et al (2020) reported that DMI increase numerically in treatments that included dry mulberry leaves in the diet. That could be due to the low NDF and high CP contents in mulberry leaves, making this forage a palatable feed for ruminants.…”
Section: Nutritional Profilementioning
confidence: 97%
“…As it has been reported in many studies that mulberry leaves could be used in livestock and poultry feeding (Sánchez, 1999;Al-Kirshi et al, 2012;Margareta et al, 2015;Wang et al, 2017a;Hao et al, 2020;Li et al, 2020;Ouyang et al, 2020;Sun et al, 2020;Wang et al, 2020a;Wang et al, 2020b;Hao et al, 2021). However, a good feedstuff should be conveniently conserved and utilized.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, mulberry leaves have become high-quality animal feed due to their high yield, low cost, good palatability and abundant protein content. As the feed of pigs, sheep, chicken broilers and other livestock, mulberry leaves can improve the conversion efficiency of feed nutrition in animals and enhance the quality of livestock and poultry products [ 7 , 8 , 9 ]. This not only alleviates the shortage of high-quality forage resources to a certain extent but also avoids the waste of mulberry-leaf resources and increases the comprehensive economic benefits of the sericulture industry.…”
Section: Introductionmentioning
confidence: 99%
“…However, mulberry leaves may contain protease inhibitors, tannic acid, lectins and other anti-nutritional factors [ 10 , 11 ]. Large additions would seriously interfere with the metabolism and absorption of feed nutrients in animals, consequently affecting animal health and the yield and quality of livestock and poultry products, which would greatly limit the development and large-scale application of mulberry leaves resources in animal feed [ 8 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%